Patent ductus arteriosus in a Newfoundland puppy - Carbonell, Cristina (2006)
Patent ductus arteriosus, or PDA, is a condition caused by failure of the fetal ductus arteriosis to functionally close within days of birth and usually results in left-to-right shunting of blood. It is one of the most commonly recognized congenital cardiac lesions in dogs, occurring more frequently in young, female dogs. In addition, breeds at risk have been recognized, including Miniature and Toy Poodles, Collies, Pomeranians, Shetland Sheepdogs, Maltese, English Springer Spaniels, Yorkshire Terriers, German Shepherds, Cocker Spaniels and Newfoundlands. Clinical signs will vary depending on size of the patency and direction of the shunt. Pups may be clinically healthy or demonstrate signs consistent with left-sided heart failure. Physical examination typically discloses hyperkinetic pulses, a continuous murmur over the left heart base and a continuous palpable thrill at the craniodorsal cardiac base. In addition, a systolic murmur is frequently evident over the mitral area. Diagnosis is based on evidence of left ventricular and atrial dilation via electrocardiography, radiography and/or echocardiography. Dilation of the main pulmonary artery and descending aorta may also be appreciated with radiography and echocardiography. Treatment consists of surgical ligation or transcatheter occlusion. The long-term prognosis for dogs treated surgically is good. Complications arise when advanced congestive heart failure or atrial fibrillation are present.